Building Infectious Disease Research Programs to Promote Security and Enhance Collaborations with Countries of the Former Soviet Union - Bartholomew, James C.; Pearson, Andrew D.; Stenseth, Nils Chr.; LeDuc, James W.; Hirschberg, David L.; Colwell, Rita R. (Frontiers in Public Health, 2015)
Addressing the threat of infectious diseases, whether natural, the results of a laboratory accident, or a deliberate act of bioterrorism, requires no corner of the world be ignored. The mobility of infectious agents and their rapid adaptability, whether to climate change or socioeconomic drivers or both, demand the science employed to understand these processes be advanced and tailored to a country or a region, but with a global vision. In many parts of the world scientific capacity has not kept pace with the need, and has left these regions and hence the world vulnerable to infectious disease outbreaks. To build scientific capability in a developing region requires cooperation and participation of experienced international scientists who understand the issues and are committed to solve the issues. The Republics Georgia, formerly part of the Soviet Union provides a valuable case study for the need to rebuild scientific capacity as they are located at the crossroads where many of the world’s great epidemics began. The U.S. Cooperative Threat Reduction (CTR) Program together with the Georgian government, have worked diligently to improve the capabilities in this region to guard against the potential future risk from especially dangerous pathogens. This effort culminated in the construction of a modern containment laboratory, the Richard G. Lugar Center for Public Health Research in Tbilisi to house both especially dangerous pathogens as well as the research to be conducted on these agents. The need now is to utilize and sustain the investment made by CTR by establishing strong public and animal health science programs tailored to the needs of the region and the goals for which this investment was made. Here we provide the analysis and recommendations of an international panel of expert scientists to provide advice to the stakeholders on the scientific path for the future. The emphasis is on an implementation strategy for decision makers and scientists to consider providing a sustainable biological science program in support of the One-Health initiative. Opportunities, potential barriers, and lessons learned while meeting the needs of the Republic of Georgia and the Caucasus region are discussed.